Identifikasi Minat Bakat Siswa Kelas 4 dan 5 pada Sistem Pakar dengan Metode Certainty Factor - Bruno Muri Beding; I Ketut Sudaryana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
An expert system is a computer program that imitates the decision-making abilities of an expert in a particular field. This system uses a knowledge base and logical rules to analyze problems and provide solutions or recommendations, helping users who do not have in-depth knowledge of the topic, then along with the development of website-based information technology which can make it easier to identify student interests, talents, especially grades 4 and 5 carried out by the teacher, this includes the potential of each individual student according to their category so as to provide an accurate solution. The aim of this research is that an application of an expert system for identification of talent interests for users is needed which supports the teacher analysis process using certainty factors, based on certainty factors which have a concept based on symptoms and diagnoses from the weight of an expert's value and the user's value, then calculated using the certainty factor formula, the output research on the creation of an expert system for identifying student talent interests using a website-based certainty factor method which produces diagnostic results for talent interest categories.